Pengendalian Ulat Grayak(Spodoptera litura ) Pada Tanaman Caisin (Brassica juncea ) Dengan Insektisida Dari Daun Suren (Toona sureni ) Dan Daun Mimba (Azadirachta indica) - Dewi (indonesia), Sinta Puspita; Sugiyarto (indoensia), Sugiyarto; Rahmiyah (indonesia), Muzayyanah (JURNAL VIGOR, 2024)
This study aims to determine the effect of vegetable insecticide formulations from suren leaf and neem leaf and the concentration of insecticides on the mortality of S. litura larvae. The study was arranged factorially (3x5) with a complete randomised design consisting of 4 replications. The first factor was an insecticide formulation consisting of 3 types, including neem leaf (A. indica), suren leaf (T. sureni), and a combination of neem leaf and suren leaf.The second factor is the concentration of insecticides, each being 0%, 25%, 50%, 75%, and 100%. The observation parameters used were the characteristics of death, mortality rate, and total mortality of larvae. The highest mortality rate and total mortality of 100% was found in the combined insecticide treatment at 75% and 100% concentration with a mortality rate of 2.47 larvae/day and 2.37 larvae/day.